The Haini Bundle / Batrisyia Azhar ... [et al.] - Azhar, Batrisyia; Mohamad Yazi, Nurul Ainil Huda; Ridzuan, Siti Nur Ain; Mohd Faudzi, Muhammad Izz Iman; Hasni, Muhammad Haziq (2021)
This business plan will introduce about THE HAINI BUNDLE that will be focusing on selling bundle or used item that can be used again. This business are one of the way to help the less capable individual person around the Malaysia. THE HAINI BUNDLE will be offering to the individual of buying the product from starting at the lowest price (RM5) to maximum price that they will offer (RM75). All the item that will be selling is form the tops of the head until the foot which is the caps, t-shirts, sweatshirts, hoodies, jackets, jeans, shorts, skirts, high-cut shoes, sandals, sport shoes and boots. All these item will be selling are below RM100. This will help the less capable individual to purchase and can get into fashionable life. Those item from THE HAINI BUNDLE are UNISEX and from the kids to the elders can buy the item from this bundle shops. This is because there’s no restriction for under age individual or there is no rules stated that only the fashionista person only can buy. There for THE HAINI BUNDLE target everyone can buy the goods from their store.